2014
DOI: 10.1038/aps.2014.112
|View full text |Cite
|
Sign up to set email alerts
|

Tanshinone IIA therapeutically reduces LPS-induced acute lung injury by inhibiting inflammation and apoptosis in mice

Abstract: Geraniol (GOH), a special type of acyclic monoterpene alcohol, has been widely used to treat many diseases associated with inflammation and apoptosis. Acute lung injury (ALI) is a common clinical disease in humans characterized by pulmonary inflammation and apoptosis. In the present study, we investigated the protective effects of GOH in a mouse model of ALI induced by the intranasal administration of lipopolysaccharide (LPS) and elucidated the underlying molecular mechanisms in RAW 264.7 cells. In vivo, GOH t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 50 publications
4
48
0
Order By: Relevance
“…This seemingly bimodal effect of Tanshinone IIA has been leveraged to kill cancer cells at high doses, but to protect parenchymal cells at much lower doses. The dose of Tanshinone IIA used in this study was very low (50 mg/kg/d) and had been reported by other studies to be safe2355. No noticeable adverse effect was noted in our animals, according to the observation of body weight, daily behavior and activity and to the analysis of other organ specimens.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…This seemingly bimodal effect of Tanshinone IIA has been leveraged to kill cancer cells at high doses, but to protect parenchymal cells at much lower doses. The dose of Tanshinone IIA used in this study was very low (50 mg/kg/d) and had been reported by other studies to be safe2355. No noticeable adverse effect was noted in our animals, according to the observation of body weight, daily behavior and activity and to the analysis of other organ specimens.…”
Section: Discussionmentioning
confidence: 51%
“…In contrast to the arguable effect on apoptosis, Tanshinone IIA has been reproducibly demonstrated to possess a potent anti-inflammatory activity in animal models of diverse diseases, including chronic kidney disease, ischemic brain injury, endotoxin-associated acute lung injury, ischemic heart disease and atherosclerosis19235556. However, it is largely unknown whether Tanshinone IIA is also beneficial in AKI or whether Tanshinone IIA is able to alter inflammatory injuries in AKI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NF-κB is required for maximal transcription of many cytokines, including pro-inflammatory mediator tumor necrosis factor (TNF)-α, and interleukin (IL)-1β. These cytokines are activated by bacterial endotoxin via NF-κB signaling and released in the early stage of ALI [5][6][7]. Besides, the dysregulation of apoptotic pathways is thought to play an important role in the pathogenesis of ALI for the loss of normal functional cells in the lung.…”
Section: Introductionmentioning
confidence: 99%
“…TSA has been demonstrated to exhibit potent anti-inflammatory properties in different cell types, such as RAW 264.7 cells [21], BV-2 cells [22], and osteoclast progenitor cells [23]. Meanwhile, its beneficial anti-inflammatory effects are also observed in different animal models [24][25][26]. Moreover, previous studies demonstrate that TSA exert a series of biochemical effects through its antioxidative [27] and anti-apoptotic [28] properties in addition to it potent anti-inflammatory effect.…”
Section: Introductionmentioning
confidence: 99%